PTH-040 Endoscopic duodenal mucosal resurfacing in type 2 diabetes – a single centre experience. (8th June 2018) - Magee, Cormac; Everson, Martin; Mok, Jessica; Makaronidis, Janine; Argentesi, Giulia; Thorpe, Sally; Vythelingum, Pajany; Pucci, Andrea; Batterham, Rachel; Haidry, Rehan
Abstract : Introduction: Evidence from bariatric surgical procedures (e.g. Roux-en-Y gastric bypass) suggests that the duodenum plays a crucial role in glycaemic control in patients with Type 2 Diabetes (T2DM). Duodenal mucosal resurfacing (DMR), a novel endoscopic therapy that resurfaces the duodenal mucosa via hydrothermal ablation, exerts an insulin-sensitising effect likely through modification of nutrient-mucosa signalling. DMR involves placing a catheter in the proximal duodenum distal to the papilla under endoscopic and fluoroscopic guidance. The duodenal mucosa is injected with saline to 'lift' it and a balloon is inflated with water and heated to 90°C to circumferentially ablate the mucosa for 10 cm. We describe the first series of patient cases from the UK treated with DMR at at University College London Hospitals (UCLH). Methods: Cases were derived from two clinical studies: REVITA 1 a single arm, open-label multi-centre in T2DM, and the open-label phase of REVITA-2 an internationl, multi-centre, randomised, double-blinded, sham controlled study in T2DM. Eligible paitents were adults with T2DM and HbA1c of 7.5%–10.0% on ≥1 oral glucose lowering medication. Baseline blood tests were collected and following a 4–6 week run-in period, patient's were treated with the DMR procedure. Patients received dietetic advice were given a specific 2 week post procedure diet. Blood tests were analysed at regular intervals following the procedure to assess changes in HbA1c over time. Hepatic transaminases were also measured and calulations were made for Homeostasis Model Assessment index (HOMA-IR) – a measure of insulin resistance. Information on adverse events was recorded at each visit. Results: A total of 11 patients (n=5 female, 58±11 years) were treated with DMR at UCLH from May 2015 – Dec 2017. Mean (±SEM) change in HbA1c at 3 months post DMR was 0.5% (±0.2) for all patients and −0.7% (±0.2 when one patient was excluded for whom gliclazide had to be stopped due to symptomatic hypoglycaemia in the month following DMR. A total of 5/11 patients completed 6 and 12 months of follow-up with mean changes in HbA1c of −1.3% and −1.5% respectively. Favourable directional changes were also observed in HOMA-IR and hepatic transaminases. Patients tolerated the procedure well and no SAEs or UADEs were reported. Two of the eleven patients (18%) patients experiencing transient constipation. Conclusion: Based on our centre's experience, DMR appears to provide a safe and effective method of improving glycaemic control in patients with T2DM. We contintue to enrol patients in the REVITA-2 trial and the results of this study will be crucial in determining the effectiveness and durability of DMR.